UPAYA PENINGKATAN LITERASI SISWA MELALUI KOMPETISI MENULIS ESAI TINGKAT SLTA SE-SUMATERA BARAT - Mezia Kemala Sari; Efri Yoni; Bahren Bahren (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Essay writing is a valuable activity for expressing ideas and concepts in a written form. On the other hand, literacy is an essential skill in comprehending, expressing, and analyzing information. Many students need help with literacy, which can impact their ability to comprehend texts and effectively convey ideas. The approach of essay writing competitions has proven to be an effective way to enhance students' literacy skills. This activity aims to motivate high school students in West Sumatra to engage in literacy activities actively. This involves a writing competition, employing methods such as distributing competition flyers across various social media platforms like Instagram, Facebook, Twitter, and WhatsApp, as well as sending letters to accessible schools. To stimulate participants' interest and socialize and develop selected sub-themes, the activity procedures include writing workshops conducted by renowned writing coaches like Ahmad Fuadi, an Indonesian bestselling author, and Rilda Taneka, an Indonesian literary figure. The outcomes of this activity include broadening perspectives, enhancing logical thinking, and improving the ability to articulate opinions with relevant sources. The essay writing competition has a positive impact on increasing students' interest in writing, evidenced by the substantial number of submissions received, all meeting initial criteria such as originality, alignment with the theme, and adherence to the stipulated rules, before being assessed by the judges. This indicates participants' understanding of the competition rules, initially driven by their interest to participate. Looking ahead, it is hoped that there will be more opportunities for students across various educational levels to compete in literacy-related fields.